1996
DOI: 10.1046/j.1365-2869.1996.d01-71.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of activity‐based techniques to identify transient arousal in respiratory sleep disorders

Abstract: SUMMARY Daytime sleepiness and impaired cognitive function can be a consequence of recurrent transient arousal from sleep. Arousal is often associated with abrupt changes in the electroencephalogram (EEG), and such changes can be used as an index of sleep disturbance, but EEG analysis is laborious and requires trained observers. Possible alternative indices of arousal not reliant on EEG analysis were investigated. Recordings were made from 36 sleeping subjects who were being investigated for sleep-related brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…It has been shown that this is caused by disturbed sleep architecture due to arousals [4,5], In unaffected people, sleep disturbances similar to that in obstructive sleep apnea result in the same impairment in vigilance [6], Arousals may not be found during electroen cephalography, and are sometimes only detectable by monitoring the autonomic system [7], Arousals with symptoms similar to those in obstructive sleep apnea can also occur in patients with partial obstruction of the upper airways, usually called 'heavy snoring disease' or 'upper airway resistance syndrom' [8]. In these patients, the diag nosis of obstructed upper airways -in contrast to central breathing disorders -is reliably made with an esophageal catheter [9], Reduction in the chemosensitivity to CO2 is never seen in isloated sleep apnea syndromes without hypoventilation [10].…”
Section: Apneamentioning
confidence: 99%
“…It has been shown that this is caused by disturbed sleep architecture due to arousals [4,5], In unaffected people, sleep disturbances similar to that in obstructive sleep apnea result in the same impairment in vigilance [6], Arousals may not be found during electroen cephalography, and are sometimes only detectable by monitoring the autonomic system [7], Arousals with symptoms similar to those in obstructive sleep apnea can also occur in patients with partial obstruction of the upper airways, usually called 'heavy snoring disease' or 'upper airway resistance syndrom' [8]. In these patients, the diag nosis of obstructed upper airways -in contrast to central breathing disorders -is reliably made with an esophageal catheter [9], Reduction in the chemosensitivity to CO2 is never seen in isloated sleep apnea syndromes without hypoventilation [10].…”
Section: Apneamentioning
confidence: 99%
“…Similarly, the majority of movements during sleep were not associated with an arousal (only 17.5% of wrist movements). Therefore, in accordance with adult data presented by Drinnan et al [181], the paediatric data does not support the theory that arousals consistently coincide with body mobilisation. Furthermore, only some movements that occur during sleep periods can be explained by arousals.…”
Section: Movement and Transient Arousalsupporting
confidence: 46%
“…Further to this, Mograss et al [180] only identified movement using chin and arm EMG, which records muscle activation, not necessarily specific movement types. Drinnan et al [181] evaluated the ability of some physiological markers to detect transient arousals from sleep in 36 adults using raw wrist and ankle accelerometry and left and right tibia EMG. They found that limb movement is somewhat correlated with arousal events and therefore can identify the occurrence of arousals.…”
Section: Discussionmentioning
confidence: 99%
“…Before and after the artifact, normal respiration cycles are visible. It is known that sudden arousals or short awakenings are potential sources for such type of artifacts since they are often accompanied by body movements causing artifacts in the RE [8]. Also apnoe/hypopnea events followed by sudden hyperpnea are likely to distort the respiratory signal shape [12] and may indicate an onset of wakefulness [11].…”
Section: Methodsmentioning
confidence: 99%
“…for the discrimination of REM and non-REM sleep [7]. Drinnan et al [8] showed that there is a phase change between ribcage and abdominal respiratory effort (RE) signals that are related to apnoe-related arousals. On the other hand, since those belt are very sensitive to movements and interactions, they are also useful to detect motion artifacts, e.g.…”
Section: Introduction and Objectivesmentioning
confidence: 99%